Influence of Graphite, Boron, Zirconium, and Hydroxyapatite Reinforcements on the Mechanostructure of Polyaryletheretherketone-Matrix Hybrid Composites - Aksakal, Bunyamin; Macit, Cevher Kursat; Er, Yusuf; Ayik, Merve (Mdpi, 2026)
Polyether ether ketone (PEEK) is a high-performance thermoplastic with potential applications in aerospace, automotive, and biomedical components, owing to its exceptional specific strength, thermal stability, and biocompatibility. However, its moderate hardness and limited wear resistance in dry sliding severely constrain its use in highly loaded tribological contacts. In this study, PEEK-based reinforced hybrid composites were produced utilizing a powder metallurgy technique, with reinforcement fractions of 10 wt.% graphite (Gr), boron (B), hydroxyapatite (HAp), and zirconium (Zr). The processing sequence included homogeneous wet-mixing, uniaxial cold compaction at pressures of 10-30 MPa, and sintering at 250-300 degrees C. The composition and microstructures were characterized by X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX). Mechanical and tribological performances were assessed by Vickers microhardness, uniaxial compression and dry sliding wear tests. The best-performing Gr-B hybrid composite increased hardness by 240% and compressive strength by 175% compared with unreinforced PEEK. Tribologically, boron-containing PEEK demonstrated up to a 34.7% reduction in the coefficient of friction and approximately a 90% drop in wear-induced mass loss compared with unreinforced PEEK. The resulting Gr-B-reinforced PEEK hybrids are excellent choices for demanding load-bearing and tribological components like aerospace bushings, automotive sliding elements, spinal cages, and orthopedic fixation devices in biomedical applications because of their balanced combination of high hardness, superior wear resistance, and high compressive strength.
Keywords: polymer; hybrid composite; PEEK; graphite-boron-zirconium; mechanostructural properties